Executive compensation, individual-level tax rates, and insider trading profits - Goldman, Nathan C.; Ozel, Naim Bugra (Journal of Accounting and Economics, 2023)
We examine whether individual-level taxes affect executives' propensity to use nonpublic information in insider trades. We predict and find a positive relation between abnormal insider trading profitability and income tax rates. Using plausibly exogenous variation in state income tax rates, we estimate that the average executive uses insider trading profits to offset between 12.2% and 19.6% of the effect that income taxes have on their net compensation. We show that the sensitivity of these profits to tax rates varies predictably with the executives' compensation and shareholdings, firm monitoring effectiveness, and information asymmetry between insiders and outside investors. We also demonstrate a positive association between SEC enforcement actions and tax rates, suggesting that tax-rate-driven changes in abnormal trading profits expose insiders to legal risk. We find that insider trading volume exhibits little sensitivity to tax rates. Our findings show that income taxes affect executives’ tendency to use private information in their trades.